2013
DOI: 10.1097/cad.0b013e328357f687
|View full text |Cite
|
Sign up to set email alerts
|

Steroidal esters of the aromatic nitrogen mustard 2-[4-N,N-bis(2-chloroethyl)amino-phenyl]butanoic acid (2-PHE-BU)

Abstract: On the basis of the results of in-silico predictions and in an effort to extend our structure-activity relationship studies, the aromatic nitrogen mustard 2-[4-N,N-bis(2-chloroethyl) amino-phenyl]butanoic acid (2-PHE-BU) was synthesized and conjugated with various steroidal alcohols. The resulting steroidal esters were evaluated for their in-vivo toxicity and antileukemic activity in P388-leukemia-bearing mice. The new derivatives showed significantly reduced toxicity and marginally improved antileukemic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…N , N ‐bis(2‐chloroethyl)‐1,4‐phenylenediamine, which belongs to aromatic N ‐mustard, has been researched in antitumor field for its good performance . It was found that the length of the spacer between the carrier part and alkylating part could influence their antitumor potency.…”
Section: Introductionmentioning
confidence: 99%
“…N , N ‐bis(2‐chloroethyl)‐1,4‐phenylenediamine, which belongs to aromatic N ‐mustard, has been researched in antitumor field for its good performance . It was found that the length of the spacer between the carrier part and alkylating part could influence their antitumor potency.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorambucil is a DNA alkylating agent belonging to the nitrogen mustard class of anticancer agents; it can form covalent adducts with the nucleobases of the DNA, alkylating the nucleobases adenine and guanine at the nitrogens N3 and N7 [18,19]. As in the case of cisplatin, DNA cross-linking induced by chlorambucil prevents DNA replication and transcription, leading to cell death (Scheme 1) [20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Despite their lethal properties, mustard gases have attracted a great interest as versatile electrophiles in inorganic and organic synthesis also employed for the preparation of numerous pharmaceutical intermediates …”
Section: Introductionmentioning
confidence: 99%